One Year Outcomes After Percutaneous Coronary Intervention in Diabetics With Stable Ischemic Heart Disease: A Single-Center Comparative Study - Adil, Muhammad (Cureus, 2021)
Introduction Coronary artery disease is the leading cause of death not only in Pakistan but also worldwide. Coronary artery disease is prevalent in diabetes and is the major cause of morbidity and mortality. This study aims at comparing the long-term outcomes of patients with and without diabetes undergoing percutaneous coronary interventions (PCI) in in a tertiary care hospital. Methods This is a prospective study including 200 patients undergoing PCI for stable ischemic heart disease. All the patients were followed up over three, six months, and then over one year for major outcomes, including death, nonfatal myocardial infarction, and revascularization, including target vessel revascularization (TVR), and target lesion revascularization (TLR), as well as the outcome of a major adverse cardiovascular event (MACE). Results The mean age (standard deviation) of the non-diabetic with stable ischemic heart disease (SIHD) patients was higher (57.4±8.9 years) than diabetes mellitus (DM) patients. All baseline characteristics were not statistically significant between the two groups. Triple vessel disease prevalence was more in DM than in the non-DM patients with SIHD, although it was not statistically significant. The number of stents implanted per patient (2.8±0.7 vs 1.9±0.8) was more in DM patients than in non-DM patients with SIHD. In-hospital adverse outcomes, including death due to cardiovascular causes, periprocedural myocardial infarction, hyperacute stent thrombosis, and bleeding complications, were insignificant between the two groups. Contrast-induced nephropathy was more prevalent in diabetics with SIHD. Although one-year major adverse cardiovascular outcomes were common in the diabetic group, these were statistically insignificant. Conclusion PCI for complex lesions in stable ischemic heart disease, both with and without diabetes, is associated with favorable in-hospital and long-term outcomes with regards to MACE and ischemia-driven revascularization.